Standardization of method and time of grafting on pecan (Carya illinoensis) under intermediate agro-climatic conditions - MEHTA, GAGAN; KUMAR, RAJESH; BAKSHI, PARSHANT; WALI, V K; JASROTIA, AMIT; KUMAR, RAKESH; BHUSHAN, BHARAT; BHAT, D J (The Indian Journal of Agricultural Sciences, 2018)
A study was conducted to standardize the method and time of grafting on pecan (Carya illinoensis Wangenh). Three grafting method, viz. Tongue grafting, Cleft grafting and Side grafting with four different timings, viz. 4th week of February, 1st week of March, 2nd week of March and 3rd week of March were used. The results indicated that among all the grafting methods, tongue grafting performed during 1st week of March showed highest grafting success (69.16 %) and maximum survival percentage (47.33 %), maximum number of leaves (24.55), plant height (118.38 cm), diameter of rootstock (2.40 cm), diameter of scion (2.19 cm), plant biomass (131.37 g) and leaf area (193.66 cm2). Hence, the grafting performed during the 1st week of March showed better performance as compared to other dates of grafting.